Biomaterial constructs for delivery of multiple therapeutic genes: a spatiotemporal evaluation of efficacy using molecular beacons. - Jennifer C Alexander; Shane Browne; Abhay Pandit; Yury Rochev (PLoS ONE)
Gene therapy is emerging as a potential therapeutic approach for cardiovascular pathogenesis. An appropriate therapy may require multiple genes to enhance therapeutic outcome by modulating inflammatory response and angiogenesis in a controlled and time-dependent manner. Thus, the aim of this research was to assess the spatiotemporal efficacy of a dual-gene therapy model based on 3D collagen scaffolds loaded with the therapeutic genes interleukin 10 (IL-10), a potent anti-inflammatory cytokine, and endothelial nitric oxide synthase (eNOS), a promoter of angiogenesis. A collagen-based scaffold loaded with plasmid IL-10 polyplexes and plasmid eNOS polyplexes encapsulated into microspheres was used to transfect HUVECs and HMSCs cells.The therapeutic efficacy of the system was monitored at 2, 7 and 14 days for eNOS and IL-10 mRNA expression using RT-PCR and live cell imaging molecular beacon technology. The dual gene releasing collagen-based scaffold provided both sustained and delayed release of functional polyplexes in vitro over a 14 day period which was corroborated with variation in expression levels seen using RT-PCR and MB imaging. Maximum fold increases in IL-10 mRNA and eNOS mRNA expression levels occurred at day 7 in HMSCs and HUVECs. However, IL-10 mRNA expression levels seemed dependent on frequency of media changes and/or ease of transfection of the cell type. It was demonstrated that molecular beacons are able to monitor changes in mRNA levels at various time points, in the presence of a 3D scaffolding gene carrier system and the results complemented those of RT-PCR.